MAZHAB GOOGLE: Nalar Fikih Generasi Z dan Fatwa Shopping di SMAN 2 Lamongan dan MA “Matholi’ul Anwar” Lamongan - Abdulloh Faqih (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
This research is motivated by the phenomenon of the presence of the internet era which is accompanied by the increasingly massive penetration of social media in various aspects of life so that the emergence of adherents of the Google school is the mainstream way of understanding Islam for the current generation Z. The research method uses a qualitative approach with a multi-site study type of research. The data collection technique used was observation, in-depth interviews and documentation of Generation Z who were at MA